The emergence of modern civil police in Scotland: a case study of the police and systems of police in Edinburghshire 1800-1833 - McGowan, John (1997)
The Police in Britain have been a focus for academic research over a number of decades but there is a dearth of historic authority about the service north of the border. Lack of information is lamentable, for Scotland through its own legal institutions entrenched in the Treaty of Union, has developed a distinct system of criminal justice and a Police service with unique democratic features. Prior to the Union of the Crowns, the crowner in Scotland was the local enforcement officer under the direction of the Sheriff who apart from administrative functions, was responsible for maintaining law and order in the Shire. James VI introduced Justices of the Peace and constables in Scotland by legal transplant. As the metropolis, Edinburgh had constables appointed from 1611 before an APS in 1617 led to their introduction throughout the kingdom. For almost two centuries the traditional role and responsibilities of constables north and south of the border, developed along similar lines but under different forms of judicial control and direction. Whereas in England local judicial authority lay with JP's, in Scotland their legal status remained below that of the Sheriff in the shire and the Bailies in burgh towns. Despite the popular myth that modern Police was established by the London Metropolitan Police Act in 1829, this thesis describes how the salient features of the modern civil Police and system of police developed earlier in Scotland, primarily through a series of local Edinburgh Police Acts obtained in 1805, 1812 and 1822. On the premise that modern police are a full time paid Force; bureaucratically organised under an operational command and control structure separate from judicial direction; and subject to both the rule of law and democratic accountability. The efforts of Patrick Colquhoun as a Police reformer were more tangible in early 19th century Edinburgh than London or indeed Dublin. Although subsidiary themes such as local financing, internal management, use of informants, prisoner care and even the purpose of the uniform in a preventive Police regime are considered, the thesis concludes under a revisionist explanation that modern Police emerged as a logical outcome of the perceived need for more effective law enforcement and wider order maintenance, consequential to the process of urbanisation. Necessity coupled with increased wealth, eventually undermined resistance to introduce new local financial burdens in other areas, hence the introduction of the new Police was piecemeal and uneven throughout Britain during the 19th century